Pengaruh Kompetensi dan Kecerdasan Emosional Terhadap Kinerja Karyawan dengan Kepemimpinan Sebagai Variabel Intervening pada Pt. Bintang Ujung Kulon Mandiri (BUKM) - Yasir Rusadi, Achmad; Muhtadin, Imam; Husainah, Nazifah; Hasanah, Hasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to find out and analyze the influence of competence and leadership on employee performance with work motivation as a mediating variable in PT. Bintang Ujung Kulon Mandiri. The method in this study uses an associative method with a quantitative research approach. Meanwhile, the number of samples used was 52 respondents, using saturated samples for the sampling method. The analysis method used is SEM-PLS. The results of the study indicate that, (1) competence has a significant influence on employee performance, (2) emotional intelligence has a significant influence on employee performance, (3) competence has a significant influence on leadership, (4) emotional intelligence has a significant influence on leadership, (5) leadership has a significant influence on employee performance, (6) competence has a significant influence on employee performance through leadership, and (7) emotional intelligence has a significant influence on employee performance through leadership.